(untitled) (Educa Journal of Studies, 2026)
The article discusses the methodological foundations of improving the process of preparing future engineers for professional activity through the use of media education tools. The study analyzes the role of digital technologies, interactive media resources, virtual laboratories, simulators and multimedia educational complexes in engineering education. The didactic possibilities of media education - visualization, modeling, remote formation of practical skills, as well as methods that focus on solving engineering problems based on a creative approach - are substantiated.